2018
DOI: 10.1016/j.drugalcdep.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

“Feeling confident and equipped”: Evaluating the acceptability and efficacy of an overdose response and naloxone administration intervention to service industry employees in New York City

Abstract: Background: The problem of injection drug use in public bathrooms has been documented from the perspectives of people who inject drugs and service industry employees (SIEs). Previous studies suggest that SIEs are unaware of how to respond to opioid overdoses, yet there are no behavioral interventions designed for SIEs to address their specific needs. In response to this gap in the field, we constructed, implemented, and evaluated a three-module behavioral intervention for SIEs grounded in the Information-Motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Nightlife management and staff are uniquely positioned for overdose response as they may be likely to encounter substance use in their venue’s on-premises toilets (Wolfson-Stofko et al, 2017). In line with previous research on the acceptability of overdose response and naloxone administration training among NYC service industry employees (Wolfson-Stofko et al, 2018), our findings confirmed venue management were receptive to integrating overdose prevention messaging and naloxone distribution into their venues’ operations.…”
Section: Discussionsupporting
confidence: 90%
“…Nightlife management and staff are uniquely positioned for overdose response as they may be likely to encounter substance use in their venue’s on-premises toilets (Wolfson-Stofko et al, 2017). In line with previous research on the acceptability of overdose response and naloxone administration training among NYC service industry employees (Wolfson-Stofko et al, 2018), our findings confirmed venue management were receptive to integrating overdose prevention messaging and naloxone distribution into their venues’ operations.…”
Section: Discussionsupporting
confidence: 90%
“…These findings highlight the benefits of designing training tailored to restaurant and service industry workers, who are often in close proximity to the overdoses (Wolfson‐Stofko et al., 2017, 2018). The present study indicates individual‐level improvements in both knowledge and attitudes based on attending workplace training (Allen et al., 2020; LaSane et al., 2022; Wolfson‐Stofko et al., 2018). It also revealed aspects of the OEND training sessions that could be improved upon in the future.…”
Section: Discussionmentioning
confidence: 81%
“…Bar, music venue, and restaurant service industry workers are uniquely positioned to reduce preventable opioid overdose deaths. They are on the frontlines of overdose identification and response, yet there have been few efforts to train them (Allen et al., 2020; LaSane et al., 2022; Wolfson‐Stofko et al., 2018). To remedy this situation, Allen et al.…”
Section: Oend Training In the Service Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that non-opioid users hold overall positive opinions of naloxone. [12][13][14] A survey of lay persons found that while only 61% of respondents had heard of naloxone, most respondents (88%) felt naloxone was beneficial in preventing accidental opioid overdoses. 12 Both medical professionals and state government agencies support efforts to increase naloxone availability due to demonstrated benefits in reducing opioid overdose mortality.…”
Section: Discussionmentioning
confidence: 99%